Passiflora foetida Linn: efeitos farmacológicos e toxicológicos - Carneiro, Antonio Benito (1996)
The pharmacological and toxicological effects of the hydro-alcoholic extracts of flowers and leaves of Passiflora foetida, popularly known as “maracuja de estalo” and inaracuja fedorente”were invertigated in vivo and in vitro. The hydro-alcoholic extracts of the leaves of this plant in the concentrations of 200 and 1.600 ppm presented potent ictiotoxic effects with a lethality of 100% in 12±4.4 min (higher concentrations), in the lebistes species. However these extracts did not show any lethal effects on mice, in hih doses (250 to 1000 mg/kg), by I P route. Nevertheless, with these doses we verified, sleepness, ataxia, motor incoordenation and in higher doses, the animais presented a previous excitation which was followed by a profound sedative State. In dogs anaesthetized by pentobarbital (30 mg/Kg), when the leafe extracts were collected during the dry season they were able to promote a fali in blood pressure (Control = 121.0±3.3) to (drug = 86.2± 4.9 mm Hg and these hypotensive effects were prolonged for = 4.9±1.3 min. On the other hand, these hypotensive effects were sensibly reduced with the leafe extracts collected during the rainy season. In the study of antagonists of this hypotensive effects we have used atropine and propranolol, drugs which were not able to inhibit these effects. The extract inhibited also the intestinal tonus while the flower extracts presented an intense peristaltic activity, with tachyphylatic effects well demonstrated. Electrokardiographic studies in rats demonstrated that the extracts in the dose of 3,2 mg/Kg presented reversível bradycardia, followed by a ventricular blockade and deformations of the ST segment, an observation that lasted for 8-10 min. and was evident at aVR derivation. The extract promoted relaxation with leafes collected during the dried season while the specimens obtained during the rainy season had no effects or some form of contractions. On the other hand the extract revealed an evident antagonism to the tonic actions of serotonin. The flowers of Passiflora foetida L. demonstrated a capacity to contract the ileal muscle in a dose dependent fashion which was antagonized by anti-serotonergic components. Studies demonstrated prolonged sleepines induced by pentobarbital in wistar rats induced by 5 to 20 mg/Kg of the dried season. This effect was dose dependent and was respectively 29, 60, 28 for experimental values of 102, 109 and 126. As for the abortive, teratogenic and fetal death actions were verified in pregnant Wistar rats. When this abortive actions were studied they revealed to be a direct on the fetal structures since we demonstrated death and fetal resorption. We could not find any luteolytic action of thee effects in these females after a histopathological analyses of the uterine material. In studies in isolated uterus of virgen female rats previounsly treated by estrogens the flower extracts of this plant promoted contractions of this preparation in the doses of 300 to 1.200 pg/ml.